Socio-economic Correlates Of Suicidality In Hong Kong - Tin , yuet (Penerbit Universiti Sains Malaysia (USM Press), 2014)
This study explores the correlates of the suicidality in Hong Kong with its socioeconomic predictors. Hong Kong witnessed its economic decline and its improvement in the last decade with 2003 as the turning point. After applying Poisson regression models on the data, it was found that individual payroll and property price indices were closely associated with the monthly suicide counts in Hong Kong, whereas unemployment rate and average rent index were not observed statistically significant. The results reinforce the findings that structural socioeconomic conditions generally have a substantial impact on suicidality and that unemployment rates may not always be correlated with suicide. This study recommends taking into account of some alternative macroeconomic variables, namely property price and individual payroll, to predict suicide rates